Contextualising and storying the Italian hostile environment: Lina Prosa's civil theatre of re-humanisation - De Michelis, Lidia; Gualtieri, Claudia (Frontiers in Human Dynamics, 2023)
This essay investigates the construction of a hostile environment for refugees and asylum seekers in Italy in recent years. Rather than a consistent set of practices, the construction of the Italian hostile environment should be interpreted as a series of uneven responses to increasing migration from the Mediterranean South, and of unsystematic concrete procedures for migration control, developed according to diverse local contexts. These specific hostile environment constructions obfuscate dehumanising practices. In this context, however, forms of civic engagement offer important examples of resistance, which we aim at bringing to the foreground in the first part of this essay. The second part addresses imaginative and artistic responses to the Italian hostile environment by focusing on the stage. In particular, Sicilian playwright Lina Prosa's The Shipwreck Trilogy (Lampedusa Beach 2003, Lampedusa Snow 2013, Lampedusa Way 2013) will be taken as case study. Representing immigration from the triple perspective of the sea voyage, the mountain limbo, and the existential "horizontal shipwreck" caused by negligent legislation, the Trilogy moves away from explicit humanitarianism or advocacy and consolidated patterns of the 'right kind' of refugee story. It celebrates, instead, migrant agency and re-mythologises the figure of the migrant as a bearer of knowledges, aspirations, affects, memories, claims, relationalities, and "better stories" (Grossberg 2019: 40).